2021
DOI: 10.1136/bmjresp-2020-000772
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and acceptability of a community pharmacy referral service for suspected lung cancer symptoms

Abstract: BackgroundLung cancer survival rates in the UK are among the lowest in Europe, principally due to late-stage diagnosis. Alternative routes to earlier diagnosis of lung cancer are needed in socioeconomically deprived communities that are disproportionately affected by poor lung cancer outcomes. We assessed the feasibility and acceptability of a community-based pharmacy referral service to encourage earlier symptomatic referral for chest X-rays.MethodsSeventeen community pharmacies located in a deprived area of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…This study, however, found that frequent purchases of the same medication were not explored fully, highlighting the potential for patients with ongoing symptoms to be missed 18. Several small-scale pilots have also found that pharmacist integration into lung cancer referral pathways is both feasible and acceptable, resulting in high-quality referrals 19 20. However, outcome data are currently very limited and barriers to successful implementation were identified to include a lack of patient awareness of such services and pharmacists’ roles, and concerns about perceived impacts on workloads.…”
Section: Discussionmentioning
confidence: 90%
“…This study, however, found that frequent purchases of the same medication were not explored fully, highlighting the potential for patients with ongoing symptoms to be missed 18. Several small-scale pilots have also found that pharmacist integration into lung cancer referral pathways is both feasible and acceptable, resulting in high-quality referrals 19 20. However, outcome data are currently very limited and barriers to successful implementation were identified to include a lack of patient awareness of such services and pharmacists’ roles, and concerns about perceived impacts on workloads.…”
Section: Discussionmentioning
confidence: 90%
“…Persistent cough was overwhelmingly the most common symptom reported (46%) 21. In the UK, three studies have evaluated initiatives to enable pharmacists to identify and refer people for chest radiography2223 or to a hospital clinic for further assessment 24. In total 69 pharmacies were involved, with 69 people referred for investigation, equating to 0.06-0.4 patients per pharmacy per month having a chest x ray examination.…”
Section: Evidence On Community Pharmacy Diagnosismentioning
confidence: 99%
“…The number of informal consultations community pharmacists deliver is increasing, and currently stands at around 20 a day, each lasting about six minutes 31. Consultations for cancer symptoms are likely to be more time consuming—for example, assessment for referral to chest radiography in pharmacy takes over twice this time 22. Even if staff in community pharmacies receive training to assess for cancer symptoms, they may not have time to deliver such consultations at scale.…”
Section: Implications For Workforce and Skills In Community Pharmacymentioning
confidence: 99%
See 1 more Smart Citation
“…Development of such pathways are likely to be complex with input from multiple stakeholders but may provide an opportunity to utilise an established network of highly accessible healthcare venues to help the NHS meet its targets around early detection of cancers. Pilot studies involving direct referral of patients with symptoms of possible lungs cancer from community pharmacies have demonstrated high levels of fidelity with national referral criteria, and high levels of patient satisfaction [19][20][21] ; further research in this area involving other malignancies, including oral cancers is needed. Online risk calculators are tools that can be used to guide clinicians in decision-making around the need for (priority) referral 22 .…”
Section: Red Flag Signs For Oral Cancermentioning
confidence: 99%